2022
DOI: 10.1038/s41598-022-18676-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anti-SARS-CoV-2 properties of essential oils and aromatic extracts

Abstract: Essential oils and aromatic extracts (oleoresins, absolutes, concretes, resinoids) are often used as food flavorings and constituents of fragrance compositions. The flavor and fragrance industry observed significant growth in the sales of some natural materials during the COVID-19 outbreak. Some companies worldwide are making false claims regarding the effectiveness of their essential oils or blends (or indirectly point toward this conclusion) against coronaviruses, even though the available data on the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…To gain structural insights and understand the binding mode of molecular structures and protein targets, we applied molecular docking processes that were previously described as an efficient in silico approach [ 60 ]. Various experiments revealed that EOs could contribute to preventing the entry of SARS-CoV-2 into the human body and investigated the efficacy of EO compounds in the prevention and treatment of COVID-19 [ 31 , 59 , 61 , 62 , 63 ]. Da Silva et al used molecular docking analysis to determine the interaction of 171 essential oil components with SARS-CoV-2, showing that the compound with the best-normalized docking score to SARS-CoV-2 Mpro was the sesquiterpene hydrocarbon (E)-β-farnesene [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To gain structural insights and understand the binding mode of molecular structures and protein targets, we applied molecular docking processes that were previously described as an efficient in silico approach [ 60 ]. Various experiments revealed that EOs could contribute to preventing the entry of SARS-CoV-2 into the human body and investigated the efficacy of EO compounds in the prevention and treatment of COVID-19 [ 31 , 59 , 61 , 62 , 63 ]. Da Silva et al used molecular docking analysis to determine the interaction of 171 essential oil components with SARS-CoV-2, showing that the compound with the best-normalized docking score to SARS-CoV-2 Mpro was the sesquiterpene hydrocarbon (E)-β-farnesene [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Molecular modeling is an interesting in silico tool used to determine the stability of compounds and the interaction types responsible for antiviral biological activity. Different EO studies revealed antiviral activity against SARS-CoV-2 [ 29 , 30 , 31 ]. Two different software were used: Surflex-Dock and UCSF chimera in UCSF Chimera 1.13.1 [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Propolis is known to disrupt the virus corroborating and has anti-coronavirus properties . Strub et al reported the extension of the skeleton length of the cinnamic acid esters to have high inhibition activity against SARS-COV-2 …”
Section: Introductionmentioning
confidence: 99%
“…Although the sophistication and complexity of EOs are undesirable properties for drug discovery, they are valuable in medical therapy and may be used as promising sources of novel drugs. Extracted compounds from EOs may be useful options against COVID-19, according to a recent study in which some signs of the inhibitory potential of EO constituents against the SARS-CoV-2 main protease have been highlighted [ 37 ].…”
Section: Introductionmentioning
confidence: 99%